Prevalence and clinical significance of co-existing mutations in MED12 and FH in uterine fibroids of Australian women - Jamaluddin, M. Fairuz B.; Nagendra, Prathima B.; Ko, Yi-An; Bajwa, Preety; Scott, Rodney J.; Nahar, Pravin; Tanwar, Pradeep S. (Frontiers in Reproductive Health, 2023)
Uterine fibroids are exceedingly common benign tumours of the female reproductive system and cause severe symptoms, including acute pain, bleeding, and infertility. Fibroids are frequently associated with genetic alterations affecting mediator complex subunit 12 (MED12), fumarate hydratase (FH), high mobility group AT-hook 2 (HMGA2) and collagen, type IV alpha 5 and alpha 6 (COL4A5-COL4A6). Recently, we reported MED12 exon 2 mutations in 39 out of 65 uterine fibroids (60%) from 14 Australian patients. The aim of this study was to evaluate the status of FH mutations in MED12 mutation-positive and mutation-negative uterine fibroids. FH mutation screening of altogether 65 uterine fibroids and corresponding adjacent normal myometrium (n=14) was carried out by Sanger sequencing. Three out of 14 patients displayed somatic mutations in FH exon 1 in addition to harbouring MED12 mutation in uterine fibroids. This study is the first to report that the mutations in MED12 and FH co-exist in uterine fibroids of Australian women.